RETRACTED: A Phase II, Single-Arm Study of Apatinib and Oral Etoposide in Heavily Pre-Treated Metastatic Breast Cancer - Hu, Nanlin; Zhu, Anjie; Si, Yiran; Yue, Jian; Wang, Xue; Wang, Jiayu; Ma, Fei; Xu, Binghe; Yuan, Peng (Frontiers in Oncology, 2021)
Introduction: We performed this clinical trial to evaluate the efficacy and safety of apatinib and oral etoposide in patients with HER2-negative locally advanced or metastatic breast cancer (MBC). Methods: Patients with HER2-negative MBC previously treated with anthracycline and taxanes and failed ≥1 prior chemotherapy regimens were recruited. The starting dose of apatinib was 500 mg and 425 mg in patients with ECOG scores of 0-1 and 2, respectively. The etoposide capsules were given at 50 mg/m2 on days 1 to 10 for 21 days. The primary end point was progression-free survival (PFS) which is assessed every 6 weeks (RECIST v1.1). Secondary end points included objective response rate (ORR), disease control rate (DCR), overall survival (OS), and safety. Results: Thirty-one eligible patients were enrolled. The median follow-up time was 11 months. The median PFS for all patients was 6.9 months (95% confidence interval (CI), 6.0–7.9), and 6.9 months (95% CI 5.3-8.6) and 6.7 months (95% CI 1.4-11.7) for patients with apatinib 425mg and 500mg once daily, respectively. The ORR was 35.5% (11/31). The DCR was 87.1% (27/31). The median OS was 20.4 months (95% CI, 11.4–29.3). The median PFS of patients who had hypertension and proteinuria was longer than that for those without hypertension and proteinuria. The most common grade 3/4 treatment-related AEs were hypertension (12/31, 38.7%), fatigue (3/31, 9.7%), thrombocytopenia (3/31, 9.7%). Conclusion: Apatinib combined with etoposide capsules is effective and tolerable in heavily pretreated, metastatic HER2-negative breast cancer patients. A lower apatinib dose provide equivalent efficacy and reduced toxicity. Trial registration (retrospectively registered): ClinicalTrails, NCT03535961, Registered 24 May 2018, https://clinicaltrials.gov/ct2/show/NCT03535961?cond=apatinib+etoposide+breast+cancer&draw=2&rank=1